Cat litter based on lithium smelting slag as well as preparation method and application of cat litter

By mixing lithium smelting slag with other materials and preparing and treated through multiple steps, a cat litter with low moisture, good water absorption and strong deodorization effect was prepared, which solved the shortcomings of existing cat litter in water absorption, agglomeration and deodorization effects, met the cat raising needs of urban residents, and realized the recycling of waste.

CN119522836APending Publication Date: 2025-02-28GANFENG LITHIUM CO LTD

Patent Information

Application Number
CN202411624506.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing cat litter has its own shortcomings in water absorption, clumping, deodorizing effect and dust issues, and it is difficult to meet the needs of all consumers.

Method used

Cat litter based on lithium smelting slag is prepared by mixing the lithium smelting slag with bentonite, binder, preservative, additive and water, and through the steps of heating treatment, grinding, extrusion and granulation, foaming and drying.

Benefits of technology

The resulting cat litter has low moisture content, good water absorption, clumping and deodorizing effects, low powdering rate, good integrity, and short collapse time, which meets the cat raising needs of urban residents. At the same time, it realizes the effective reuse of industrial waste and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005135818400000061
    Figure BDA0005135818400000061
Patent Text Reader

Abstract

The invention provides cat litter based on lithium smelting slag and a preparation method and application of the cat litter, and belongs to the technical field of pet supplies, the cat litter based on the lithium smelting slag is obtained by modifying the lithium smelting slag at high temperature, mixing the modified lithium smelting slag with a binder, a preservative and an auxiliary agent, granulating, foaming, drying and screening. The cat litter based on the lithium smelting slag is short in collapsing time, urine and the like can rapidly permeate into the bottom layer of the cat litter, and the cat litter has good water absorption and deodorization performance; the preparation method provided by the invention not only solves the problem of treatment of the lithium smelting waste residue and reduces the risk of environmental pollution, but also provides a new raw material source for production of the cat litter and reduces the production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waste residue recycling and pet products, and in particular to cat litter based on lithium smelting slag, and a preparation method and application thereof. Background Art

[0002] The types of cat litter sold on the market include bentonite cat litter, tofu cat litter, pine cat litter, crystal cat litter, mixed cat litter, etc. Bentonite cat litter has good water absorption and clumping ability, but it produces a lot of dust and has a poor deodorizing effect; tofu cat litter has good water absorption, clumping and deodorizing effect, but it produces a lot of dust; pine cat litter, as a plant cat litter, has the advantage of being environmentally friendly and natural, but it produces a lot of dust and has poor water absorption and clumping abilities; crystal cat litter has silica gel as its main component, which has good deodorizing ability but poor clumping and water absorption abilities; all indicators of mixed cat litter are good, but its advantages are not outstanding.

[0003] Patent CN 107897009A discloses a bentonite cat litter, which is prepared by compounding bentonite, tourmaline, nano-Ti2O, hydroxyapatite, bamboo charcoal powder, etc. to increase the adsorption pore size and achieve adsorption and removal capacity. However, this method has expensive materials, high production costs for cat litter, and nano-Ti2O has certain health risks, which is harmful to cats and human health. There is no embodiment data for the deodorizing effect mentioned. Patent CN 117581797A uses rice straw powder and poplar fluff pulp as raw materials to make cat litter. Although the cat litter has improved water absorption capacity and good bactericidal effect, it has a high cellulose content and a slow decomposition rate. It cannot be dissolved in water in a short time and is easy to entangle or block the sewer pipe.

[0004] Although there are many types of cat litters on the market, each type of cat litter has its advantages and disadvantages and is difficult to meet the needs of all consumers. Therefore, developing new cat litter products and improving various performance indicators of cat litters have become an important topic in the current cat litter market. Summary of the invention

[0005] The object of the present invention is to provide a cat litter based on lithium smelting slag, and a preparation method and application thereof. The obtained cat litter based on lithium smelting slag has low moisture content, good water absorption, agglomeration and deodorization effect, low pulverization rate, good integrity and short collapse time, thus meeting the cat-raising needs of urban residents.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a cat litter based on lithium smelting slag, comprising the following raw materials in parts by weight:

[0008] 55-70 parts of lithium smelting slag, 10-20 parts of bentonite, 1-10 parts of binder, 1-5 parts of preservative, 1-5 parts of additive, and 10-20 parts of water.

[0009] Preferably, the binder includes one or more of CMC, guar gum and sodium silicate.

[0010] Preferably, the preservative includes one or more of sodium benzoate, sodium sorbate and sodium dehydroacetate.

[0011] Preferably, the auxiliary agent comprises a hydrogen peroxide solution, and the mass concentration of the hydrogen peroxide solution is 30%.

[0012] The present invention provides a method for preparing the above-mentioned cat litter based on lithium smelting slag, comprising the following steps:

[0013] The lithium smelting slag is subjected to heating treatment and grinding in sequence to obtain modified lithium smelting slag powder;

[0014] Mixing the modified lithium smelting slag powder, bentonite, a binder, a preservative, an additive and water to obtain a mixed material;

[0015] Extruding and granulating the mixed material to obtain spherical cat litter;

[0016] The spherical cat litter is foamed, dried and sieved to obtain cat litter based on lithium smelting slag.

[0017] Preferably, the heating treatment is carried out at a temperature of 300 to 600° C. and for a time of 1 to 5 hours.

[0018] Preferably, the particle size of the modified lithium smelting slag powder is 38 to 74 μm.

[0019] Preferably, the particle size of the spherical cat litter is 1 to 4 mm.

[0020] Preferably, the foaming temperature is 20-35° C., and the time is 2-4 hours; the drying temperature is 70-100° C., and the time is 25-45 minutes.

[0021] The present invention also provides the use of the cat litter based on lithium smelting slag or the cat litter based on lithium smelting slag prepared by the above preparation method in the field of pet products.

[0022] Beneficial effects of the present invention:

[0023] The present invention performs high-temperature modification on lithium smelting slag produced by lithium extraction from spodumene sulfuric acid method. The dried lithium slag loses surface and interlayer water without damaging the porous structure of the lithium smelting slag. Due to its unique pore structure, it maintains good adsorption performance, can effectively adsorb cat urine and odor, and keep the cat litter box clean and hygienic. The cat litter based on lithium smelting slag obtained by the present invention has low moisture, high water absorption rate, good agglomeration performance, low pulverization rate, good stability, good deodorization effect, short disintegration time, can make urine and the like quickly penetrate into the bottom layer of the cat litter, reduce the residence time of urine on the surface, and meet the cat-raising needs of urban residents.

[0024] The present invention converts lithium smelting slag into cat litter, with a usage amount of up to 70%, thereby achieving effective recycling of industrial waste, reducing pressure on the environment, and also reducing the production cost of cat litter; compared with chemical additives that may be contained in some traditional cat litters, the present invention uses non-toxic and harmless additives in the preparation process of cat litter based on lithium smelting slag, reducing the use of chemical substances, and being safer for pets and the environment. DETAILED DESCRIPTION

[0025] The present invention provides a cat litter based on lithium smelting slag, comprising the following raw materials in parts by weight:

[0026] 55-70 parts of lithium smelting slag, 10-20 parts of bentonite, 1-10 parts of binder, 1-5 parts of preservative, 1-5 parts of additive, and 10-20 parts of water.

[0027] In the present invention, the mass fraction of the lithium smelting slag is preferably 55-70 parts, further preferably 60-70 parts, and more preferably 65-70 parts; the present invention has no special limitation on the source of the lithium smelting slag, and it can be obtained in a manner well known in the art. In the embodiment of the present invention, the lithium smelting slag is preferably the residue discharged after leaching, filtering and washing of spodumene clinker in the process of producing lithium carbonate by spodumene sulfuric acid method, and its chemical composition includes SiO2, Al2O3 and CaO, and also contains elements such as Fe, Mg, Ca, Na, K, etc. It contains a certain amount of moisture under natural drying, and is powdery after drying. The particles are small and have a porous structure with a large internal surface area, mostly in a glassy state. The porous structure of the lithium slag enables it to have a certain adsorption capacity for water and ammonia nitrogen, which is conducive to the effective adsorption of cat urine and odor.

[0028] In the present invention, the mass fraction of the bentonite is preferably 10 to 20 parts, more preferably 10 to 15 parts, and even more preferably 10 to 12 parts.

[0029] In the present invention, the mass fraction of the binder is preferably 1 to 10 parts, more preferably 5 to 10 parts, and more preferably 5 to 8 parts; the binder preferably includes one or more of CMC, guar gum and sodium silicate, and more preferably includes CMC and / or guar gum. When the binder is two or more of the above, the present invention has no special limitation on the ratio of different types of binders, and any ratio is acceptable.

[0030] In the present invention, the mass fraction of the preservative is preferably 1 to 5 parts, more preferably 3 to 5 parts, and more preferably 4 to 5 parts; the preservative includes one or more of sodium benzoate, sodium sorbate and sodium dehydroacetate, more preferably includes one or more of sodium benzoate and sodium sorbate, and more preferably includes sodium benzoate.

[0031] In the present invention, the mass fraction of the auxiliary agent is preferably 1 to 5 parts, further preferably 3 to 5 parts, and more preferably 4 to 5 parts; the auxiliary agent preferably includes hydrogen peroxide solution, and the mass concentration of the hydrogen peroxide solution is preferably 30%. The source of the hydrogen peroxide solution is not particularly limited in the present invention. In an embodiment of the present invention, the hydrogen peroxide solution is preferably from Sinopharm Chemical Reagent Co., Ltd., AR / 500mL; hydrogen peroxide solution is unstable at room temperature, and can slowly decompose to produce water and oxygen in the process of preparing cat litter molding from lithium smelting slag, and oxygen overflows the particle body, forming tiny pores inside the particles, increasing the specific surface area of ​​cat litter particles, and more conducive to the absorption of cat urine and ammonia by cat litter particles. In this process, increasing the temperature is conducive to accelerating the decomposition of hydrogen peroxide and reducing the time used for foaming.

[0032] In the present invention, the mass fraction of the water is preferably 10 to 20 parts, more preferably 10 to 15 parts, and even more preferably 10 to 12 parts.

[0033] The present invention provides a method for preparing the above-mentioned cat litter based on lithium smelting slag, comprising the following steps:

[0034] The lithium smelting slag is subjected to heating treatment and grinding in sequence to obtain modified lithium smelting slag powder;

[0035] Mixing the modified lithium smelting slag powder, bentonite, a binder, a preservative, an additive and water to obtain a mixed material;

[0036] Extruding and granulating the mixed material to obtain spherical cat litter;

[0037] The spherical cat litter is foamed, dried and sieved to obtain cat litter based on lithium smelting slag.

[0038] In the present invention, the temperature of the heat treatment is preferably 300-600° C., more preferably 400-600° C., more preferably 450-600° C., and the time is preferably 1-5 h, more preferably 1-3 h, more preferably 1-2 h.

[0039] In the present invention, the particle size of the modified lithium smelting slag powder is preferably 38 to 74 μm, and more preferably 48 to 74 μm; the use of lithium smelting slag with a smaller particle size combined with bentonite and a binder can achieve more sufficient mixing and reaction, thereby ensuring the uniformity of the cat litter product particles and improving the strength.

[0040] In the present invention, the particle size of the spherical cat litter is preferably 1 to 4 mm, more preferably 2 to 4 mm, and even more preferably 3 to 4 mm.

[0041] In the present invention, the foaming temperature is preferably 20-35°C, more preferably 28-35°C, more preferably 28-30°C, and the time is preferably 2-4h, more preferably 3-4h; foaming the cat litter can expand the material to form a cellular structure and enhance the adsorption performance.

[0042] In the present invention, the drying temperature is preferably 70 to 100° C., more preferably 80 to 100° C., more preferably 85 to 100° C., and the drying time is preferably 25 to 45 min, more preferably 25 to 40 min, more preferably 25 to 35 min.

[0043] The present invention also provides the use of the cat litter based on lithium smelting slag or the cat litter based on lithium smelting slag prepared by the above preparation method in the field of pet products.

[0044] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0045] The 30% hydrogen peroxide solution used in Examples 1 to 3 of the present invention comes from Sinopharm Chemical Reagent Co., Ltd., AR / 500 mL; the composition and content of the lithium smelting slag used in Examples 1 to 3 are shown in Table 1.

[0046] Table 1 Composition and content of lithium smelting slag used in Examples 1 to 3

[0047] Components <![CDATA[SiO2]]> <![CDATA[Al2O3]]> CaO <![CDATA[Fe2O3]]> <![CDATA[K2O]]> MgO <![CDATA[N2O]]> <![CDATA[SO3]]> other content / % 58.54 19.34 7.34 1.44 0.28 0.73 0.25 6.28 5.8

[0048] Example 1

[0049] The lithium smelting slag was placed in a high temperature furnace and heated at 300°C for 3 hours, and then ground after natural cooling to obtain a modified lithium smelting slag powder with a particle size of 38 μm;

[0050] Mix 55 parts of modified lithium smelting slag powder, 15 parts of bentonite, 7 parts of CMC, 3 parts of guar gum, 1 part of sodium benzoate, 4 parts of 30% hydrogen peroxide solution and 15 parts of water to obtain a mixed material;

[0051] The mixture is placed in a granulator and granulated into a spherical cat litter with a particle size of 1 mm;

[0052] The spherical cat litter was maintained at 35°C for 2 hours to foam, dried at 70°C for 45 minutes, and sieved to obtain cat litter based on lithium smelting slag.

[0053] Example 2

[0054] The lithium smelting slag was placed in a high temperature furnace and heated at 450°C for 2 hours, and then naturally cooled and ground to obtain a modified lithium smelting slag powder with a particle size of 48 μm;

[0055] 60 parts of modified lithium smelting slag powder, 15 parts of bentonite, 4 parts of CMC, 4 parts of guar gum, 2 parts of sodium benzoate, 3 parts of 30% hydrogen peroxide solution and 12 parts of water are mixed to obtain a mixed material;

[0056] The mixture is placed in a granulator and granulated into a spherical cat litter with a particle size of 3 mm;

[0057] The spherical cat litter was maintained at 30°C for 3 hours to foam, dried at 85°C for 35 minutes, and particles that did not meet the standards were removed by sieving to obtain cat litter based on lithium smelting slag.

[0058] Example 3

[0059] The lithium smelting slag was placed in a high temperature furnace and heated at 600°C for 1 hour, and then naturally cooled and ground to obtain a modified lithium smelting slag powder with a particle size of 74 μm;

[0060] 70 parts of lithium smelting slag powder, 10 parts of bentonite, 3 parts of CMC, 2 parts of guar gum, 1 part of sodium benzoate, 4 parts of 30% hydrogen peroxide solution and 10 parts of water are mixed to obtain a mixed material;

[0061] The mixture is placed in a granulator and granulated into a spherical cat litter with a particle size of 4 mm;

[0062] The spherical cat litter was maintained at 28° C. for 4 hours to foam, dried at 100° C. for 25 minutes, and particles that did not meet the standards were removed by sieving to obtain cat litter based on lithium smelting slag.

[0063] Performance measurement

[0064] According to T / ZGXX 0005-2022 "Cat Litter for Pet Cleansing and Hygiene Products", the cat litter based on lithium smelting slag obtained in Examples 1 to 3 was tested for moisture, water absorption rate, agglomeration height, agglomeration weight, agglomeration strength, powder content, pulverization rate, collapse time, and deodorization effect. The test results are shown in Table 2.

[0065] Table 2 Performance measurement results of cat litter based on lithium smelting slag in Examples 1 to 3

[0066]

[0067] It can be seen from Table 2 that the cat litters based on lithium smelting slag obtained in Examples 1 to 3 have good water absorption, agglomeration and deodorization effect, low pulverization rate and good integrity, which meet the requirements of the superior grade of mixed cat litter in T / ZGXX 0005-2022 "Cat Litter for Pet Cleaning and Hygiene Products". The disintegration time of the cat litter based on lithium smelting slag of the present invention is within 20s, which is better than the dissolution effect (25s) of the commercially available tofu cat litter; the residual odor concentration after adsorption is also better than the deodorization effect of the existing bentonite cat litter.

[0068] It can be seen from the above embodiments that the present invention provides a cat litter based on lithium smelting slag. By limiting the drying conditions and time, the lithium smelting slag is directly modified at high temperature. The modified lithium smelting slag loses surface and interlayer water without damaging the porous structure of the lithium smelting slag, thereby maintaining good adsorption performance for water and ammonia. The modified lithium smelting slag is then mixed with a binder, a preservative and water to obtain a cat litter based on lithium smelting slag with complete properties, thereby solving the technical problem of the present application.

[0069] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A cat litter based on lithium smelting slag, characterized in that, The preparation comprises the following raw materials in parts by weight: 55-70 parts of lithium smelting slag, 10-20 parts of bentonite, 1-10 parts of binder, 1-5 parts of preservative, 1-5 parts of additive, and 10-20 parts of water.

2. The cat litter based on lithium smelting slag according to claim 1, characterized in that: The binder includes one or more of CMC, guar gum and sodium silicate.

3. The cat litter based on lithium smelting slag according to claim 1, characterized in that, The preservative includes one or more of sodium benzoate, sodium sorbate and sodium dehydroacetate.

4. The cat litter based on lithium smelting slag according to claim 1, characterized in that: The auxiliary agent includes a hydrogen peroxide solution, and the mass concentration of the hydrogen peroxide solution is 30%.

5. The method for preparing cat litter based on lithium smelting slag according to any one of claims 1 to 4, characterized in that: The following steps are involved: The lithium smelting slag is subjected to heating treatment and grinding in sequence to obtain modified lithium smelting slag powder; The modified lithium smelting slag powder, bentonite, a binder, a preservative, an additive and water are mixed to obtain a mixed material; Extruding and granulating the mixed material to obtain spherical cat litter; The spherical cat litter is foamed, dried and sieved to obtain cat litter based on lithium smelting slag.

6. The preparation method according to claim 5, characterized in that: The heating treatment is performed at a temperature of 300 to 600° C. and for a time of 1 to 5 hours.

7. The preparation method according to claim 5, characterized in that: The particle size of the modified lithium smelting slag powder is 38-74 μm.

8. The preparation method according to claim 5, characterized in that: The particle size of the spherical cat litter is 1 to 4 mm.

9. The preparation method according to claim 5, characterized in that: The foaming temperature is 20-35° C., and the time is 2-4 hours; the drying temperature is 70-100° C., and the time is 25-45 minutes.

10. Use of the cat litter based on lithium smelting slag according to claims 1 to 4 or the cat litter based on lithium smelting slag prepared by the preparation method according to claims 5 to 9 in the field of pet products.

Citation Information

Patent Citations

  • Bentonite cat litter and preparation method thereof

    CN107897009A

  • Animal dross absorbent and method

    CA2045105A1

  • Modification bagasse cat litter and preparation method thereof

    CN105941169A

  • Preparation method of clay-based cat litter

    CN118318740A

  • Lithium slag doped cat litter and preparation thereof

    CN118614402A

Cited By

  • Magnesium oxide slag environment-friendly cat litter and preparation method thereof

    CN120323338A